2014
DOI: 10.5897/jmpr10.737
|View full text |Cite
|
Sign up to set email alerts
|

A review on therapeutic potential of Nigella sativa (kalonji) seeds

Abstract: Nigella sativa name as black seed or Kalonji seed belongs to family of rananculacea. It is widely grown in different part of world and is an annual herb cultivated in India and Pakistan, Phytochemically; it contains fixed oil, protein, alkaloids saponin and essential oil. N. sativa has been reported to possess potent antioxidant, hepatoprotective, antiparasitic, anticancer, antidiabetic, antimicrobial, antiparasitic, analgesic and anti-inflammatory, anti-nociceptive, anti-ulcer, anti-histaminic etc. The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(15 citation statements)
references
References 33 publications
(39 reference statements)
0
15
0
Order By: Relevance
“…[7] Various medical databases reported the therapeutic effects of NS and its active metabolites in asthma. Several preclinical studies have described multiple effects of NS in animal or cellular models of asthma including bronchodilation, antihistaminic, anti-inflammatory, anti-leukotrienes, and immunomodulatory effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7] Various medical databases reported the therapeutic effects of NS and its active metabolites in asthma. Several preclinical studies have described multiple effects of NS in animal or cellular models of asthma including bronchodilation, antihistaminic, anti-inflammatory, anti-leukotrienes, and immunomodulatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that black seed or Nigella sativa has anti-inflammatory and immunomodulatory properties. [7] In several preclinical and clinical studies, Nigella sativa showed positive effects on clinical and biochemical markers of asthma inflammation. [8] The aim of this study was to investigate the effect of Nigella sativa on Th17/Treg balance, and improvement of asthma control in children with asthma.…”
Section: [2]mentioning
confidence: 99%
See 1 more Smart Citation
“…The antimalarial activity was because of antioxidant effect from the extract on Plasmodium infected mice. The study was improved to see the antioxidative status in red blood cells, and hepatocytes of infected mice were seen [46, 47]. …”
Section: Antimicrobial Effectmentioning
confidence: 99%
“…Nigella sativa seed found to be contents variety of chemicals 20 , these chemicals are significantly therapeutic in nature. -Coumarins consists of 6-methoxy-coumarin, 7-hydroxy-coumarin, 7-oxy-coumarin.…”
Section: Chemical Compositionmentioning
confidence: 99%